2012
DOI: 10.1021/jp210140j
|View full text |Cite
|
Sign up to set email alerts
|

Small- and Wide-Angle X-ray Scattering Characterization of Bulk Heterojunction Polymer Solar Cells with Different Fullerene Derivatives

Abstract: The aim of this study is to quantitatively investigate the effect of different fullerene type (PC 60 BM and PC 70 BM) on various morphological structures and power conversion efficiency (PCE) in the bulk heterojunction (BHJ) P3HT/PC x BM solar cells. The solar cells are fabricated by spin coating without thermal annealing. The quantitative investigations of three-dimensional selforganized nanostructures are performed by using combined grazingincidence small-and wide-angle X-ray scattering technique (GISAXS/GIW… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
68
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 64 publications
(73 citation statements)
references
References 35 publications
5
68
0
Order By: Relevance
“…P3HT is among the most studied model systems of conjugated polymers. It is extensively studied as a homopolymer and in blends with electron acceptor materials such as the fullerene derivative [6,6]‐phenyl‐C61‐butyric acid methyl ester (PCBM) . Today, the active layer material P3HT:PCBM is still among the most frequently studied materials in OPV, although other combinations of conjugated polymers and electron acceptor materials have shown much higher solar cell efficiencies .…”
Section: Probing the Active Layer Morphology With Giwaxsmentioning
confidence: 99%
See 1 more Smart Citation
“…P3HT is among the most studied model systems of conjugated polymers. It is extensively studied as a homopolymer and in blends with electron acceptor materials such as the fullerene derivative [6,6]‐phenyl‐C61‐butyric acid methyl ester (PCBM) . Today, the active layer material P3HT:PCBM is still among the most frequently studied materials in OPV, although other combinations of conjugated polymers and electron acceptor materials have shown much higher solar cell efficiencies .…”
Section: Probing the Active Layer Morphology With Giwaxsmentioning
confidence: 99%
“…Thus, the crystal structure of P3HT is well‐known and revisited in many studies, which include pure P3HT homopolymer as a reference system . Typically, it is important if the polymer consists of repeat units which are derived from a random isomer of the monomer (regiorandom) or of the same isomer (regioregular).…”
Section: Probing the Active Layer Morphology With Giwaxsmentioning
confidence: 99%
“…By fitting the GISAXS plots using a combination of the Debye–Anderson–Brumberger equation (DAB model) and the polydisperse spheres having Schultz size distribution with the hard‐sphere interaction between the PCBM clusters, detailed structural information can be deduced, as shown in Figure f. In a following study, Su and co‐workers further studied the system of P3HT/PCBM, and found that partial attachment between the PCBM clusters has a negative effect on the charge transport, leading to a reduction of the device performance.…”
Section: Characterizing the Lateral Phase Separation In Bhj Thin Filmmentioning
confidence: 99%
“…6 The P3HT:60PCBM blend exhibits one of the most robust microstructures within OPV. [7][8][9] However, it has a limited open-circuit voltage (Voc) and short-circuit current (Jsc) in photovoltaic devices. 10 We have recently shown that solar cells using an alternative small molecule non-fullerene acceptor (NFA), IDTBR, when mixed with P3HT, can achieve power conversion efficiencies of up to 6.4%.…”
mentioning
confidence: 99%